2010
DOI: 10.1111/j.1471-1842.2010.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Internet health literacy of HIV‐positive people through the provision of a computer and Internet health education intervention

Abstract: Objective: The objective of this study was to assess perceived Internet health literacy of HIV-positive people before and after an Internet health information educational intervention. Methods: We developed a 50-min educational intervention on basic computer skills and online health information evaluation. We administered a demographic survey and a validated health literacy survey (eHEALS) at baseline, immediately after, and 3 months the class. Changes in scores between the surveys were analysed. Results: Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 19 publications
3
86
0
2
Order By: Relevance
“…In fact, several barriers prevent them from making effective use of these important sources of information, such as inadequate informatics skills and poor ability to search, evaluate and use health information. 100 Consequently, Robinson and Graham 101 argued that introductory internet health information educational interventions tailored to patient affected by HIV are crucial to improve their confidence in finding and using health information resources, since they enhance the individual ability to self-manage the health condition. At the same time, community-based health information partnerships seem to be particularly effective in addressing health literacy and health information inequalities in marginalized communities.…”
Section: The Drawbacks Of Poor Health Literacy On Hiv Treatmentmentioning
confidence: 99%
“…In fact, several barriers prevent them from making effective use of these important sources of information, such as inadequate informatics skills and poor ability to search, evaluate and use health information. 100 Consequently, Robinson and Graham 101 argued that introductory internet health information educational interventions tailored to patient affected by HIV are crucial to improve their confidence in finding and using health information resources, since they enhance the individual ability to self-manage the health condition. At the same time, community-based health information partnerships seem to be particularly effective in addressing health literacy and health information inequalities in marginalized communities.…”
Section: The Drawbacks Of Poor Health Literacy On Hiv Treatmentmentioning
confidence: 99%
“…Participants were asked to rate their level of agreement with various statements, such as, "I know how to find helpful health resources on the internet," "I know how to use the health information that I find on the internet to help me," and "I can tell high-quality from low-quality health resources on the internet." The questionnaire has been previously validated on patients with HIV and health care trainees (9,10). The eHEALS survey can be scored in its entirety on the basis of the cumulative responses to eight questions (the first two eHEALS questions serve as supplementary questions to understand general interest in eHealth and are not included in overall score), or each question can be evaluated independently.…”
Section: Ehealth Literacymentioning
confidence: 99%
“…Although one RCT scored 8 of 13 [23] and one of three quasi-experimental studies scored 6 of 9, [24] they had strengthened validity of causal inferences by comparing control and intervention groups. In addition, two quasi-experimental studies scored 6 of 9 [25,26] and lacked a comparison group to determine pre-post intervention effects.…”
Section: Characterizing the Evidence Basementioning
confidence: 99%
“…Four studies were conducted in the U.S., [24][25][26][27] two in Uganda, [23,28] and one in Peru. [29] Various study designs were used: cross-sectional, [27][28][29] quasi-experimental, [24][25][26] and a RCT. [23] Two studies identified a theoretical or conceptual framework used in their research.…”
Section: Overview Of Studies Included In the Reviewmentioning
confidence: 99%
See 1 more Smart Citation